PERSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS NEGERI PADANG TENTANG TUGAS-TUGAS GURU - 791-800 , Prima Ananta Dwi Putra (Universitas Negeri Padang, 2015)
ABSTRACT Based of the lack of student interest in the teaching assignment. The purpose of this study was to determine students perceptions about the teaching assignment. This research is descriptive. Population in this research is the students of Building Engineering Education class of 2011 who follow and are listed in PPLK in half from July to December 2014. The sampling technique using total sampling as many as 52 samples of the population of 52 students. Data were collected using a questionnaire research as much as 39 point statements with Likert Scale Modification of four answer choices. From the results, the main cause of most affect the low perceptions of the students about the teaching assignment is the readiness to become a teacher at 69.47%. Aside from the readiness, other causes that affect the students' perceptions about the teaching assignment is the personality with the degree of achievement of 70.43%, amounting to 70.96% motivation, PPLK experience by 71.25%, 72.40% expectations, the willingness of 72.78%, interest amounted to 73.21%, and lastly, the low perception of the students about the teaching assignment is the order of 77.04%. The conclusion of this study, the average degree of achievement of 72.19% included in the category good enough. Keywords: Perception, Student, Teacher Assignment.